Awareness, Use, and Perceptions of Heated Tobacco Products among young adults in Germany : a cross-sectional online survey - Laxminarayan Sonde (2025)
Introduction: Aim-To assess the awareness, perception, about HTPs and prevalence of HTP usage among young adults of age 18-40 years in Germany and relationship of HTP usage with conventional tobacco usage. Methods: A cross sectional and observational Study among 246 young adults of age 18-40 years living in Germany was conducted. The tool was the questionnaire developed for the purpose of this study, collected information on demographic factors, substance use, addiction with Fagerstrom scale, Personality with big 5 inventory, perceptions and knowledge about the HTPs. Data was analysed using SPSS. Awareness, Use and Perceptions were analysed and relationship with demographic characteristics, substance use and personality were assessed. Results: About 45.9% of the participants had above or equal to average knowledge score. Men, married, people with college level education, EC and CC users showed significantly high awareness. More than one-fourth of the study participants used HTPs at least once in their lif
Keywords: Heated tobacco products; heat-not-burn tobacco products; smoking cessation; E-cigarettes; prevalence of tobacco use